Anisotropic fracture and energy dissipation characteristics of interbedded marble subjected to multilevel uniaxial compressive cyclic loading. Issue 2 (25th October 2020) - Wang, Yu; Han, Jianqiang; Ren, Junyu; Li, Changhong
Abstract: This work aims to investigate the anisotropic fracture and energy dissipation characteristics of marbles cored along an angle of 0°, 30°, 60° and 90° with respect to interbed planes and subjected to multilevel cyclic loading conditions. Rock fatigue deformation, strength, lifetime and dissipated energy first decrease and then increase with increasing interbed orientation, and they get to the minimum for the sample at a 30° interbed orientation. Rock stiffness degradation is significant with the increase of cyclic level, and the stiffness evolution is affected by the interbed structure. The incremental rate of dissipated energy becomes faster with increase of cyclic loading level, and it presents an abrupt increasing trend at the last cyclic loading level. A damage evolution model was first established based on dissipated energy to describe the two‐phase damage accumulation characteristics. It suggests that the proposed model fits to the testing data well and favourably represents the non‐linear characteristics of damage accumulation.